A case–control study to examine the association between breastfeeding during late pregnancy and risk of a small‐for‐gestational‐age birth in Lima, Peru. Issue 2 (1st October 2012) - Pareja, Rossina G.; Marquis, Grace S.; Penny, Mary E.; Dixon, Philip M.
Abstract Excessive demands on maternal nutritional status may be a risk factor for poor birth outcomes. This study examined the association between breastfeeding during late pregnancy (≥28 weeks) and the risk of having a small‐for‐gestational‐age (SGA) newborn, using a matched case–control design (78 SGA cases: birthweight <10th percentile for gestational age; 150 non‐SGA controls: 50th percentile <birthweight <90th percentile for gestational age). Between March 2006 and April 2007, project midwives visited daily three government hospitals in Lima, Peru and identified cases and matched controls based on hospital, gestational age, and inter‐gestational period. Mothers were interviewed and clinical chart extractions were completed. Factors associated with risk of SGA were assessed by their adjusted odds ratios (aOR) from conditional logistic regression. Exposure to an overlap of breastfeeding during late pregnancy was not associated with an increased risk of having a SGA newborn [aOR = 0.58, 95% confidence interval (CI): 0.10–3.30]. However, increased risk was associated with having a previous low‐birthweight birth (aOR = 6.53; 95% CI: 1.43–29.70) and a low intake of animal source foods (<25th percentile; aOR = 2.26; 95% CI: 1.01–5.04), and tended to be associated with being short (<150 cm; aOR = 2.05; 95% CI: 0.92–4.54). This study found no evidence to support the hypothesis that breastfeeding during late pregnancy increases the risk for SGA; however, studies with greater statistical power are needed to definitively examine this possible association and clarify whether there are other risks to the new baby, the toddler and the pregnant woman.